Lignin removal from synthetic wastewater via Fenton-like reaction over Cu supported on MCM-41 derived from bagasse: Optimization and reaction intermediates - Pongsert Sriprom; Sutasinee Neramittagapong; Chitsan Lin; Arthit Neramittagapong; Pornsawan Assawasaengrat (My University, 2023)
Lignin degradation was performed using a Fenton-like oxidation reaction with Cu supported on MCM-41, derived from bagasse (Cu-BG-MCM-41), as the catalyst. The optimal degradation conditions required to remove a predetermined amount of lignin (95%) from an effluent were determined. Based on the literature review and preliminary tests, the critical parameters determining the operating conditions include temperature, catalyst loading, pH, H2O2 concentration, and reaction time. The experimental design and working conditions were based on Box–Behnken design. The reaction products were analyzed via UV–vis and gas chromatography-mass spectrometry. Response surface methodology (RSM) was used to predict the optimum operating conditions for the Fenton-like reaction for 95% lignin degradation, which were a temperature of 80 °C, initial pH of 9, H2O2 concentration of 1 mL/L, catalyst loading of 1.0 g/L, and reaction time of 30 min. These conditions were validated three times and the achieved percentage of lignin degradation was 95 ± 2%. This is close to the value of 95% used in the RSM to determine the optimum operating conditions, thus verifying the model. The catalyst was stable and functioned well under the optimum design conditions. Moreover, the reaction could be used to obtain high-value intermediate products if stopped after 5 min. Finally, lignin was degraded into vanillin, a higher-value product. As expected, the proposed Fenton-like approach expanded the pH working range from less than 4 to 5–9.
Keywords: Bagasse; Nanomaterials for catalytic reactions